Design of Analytical energy consumption model for data transfer over wireless links - Ananda Venkatesan, B; Purushottam, P (International Journal of Engineering and Technology, 2018)
This project investigates about the lowering of vitality utilization in group based remote sensor systems(WSNs). It uses Clustering technique and QPSK methods to lower the energy consumption of nodes in WSNs. This approach has a big advantage to prolong the lifetime of the WSN. The results show that clustering reduces traffic flow, limits vitality utilization, and broaden the lifetime of the sensor network. This project is also implemented with security, effective communication by using set ibs protocol.Â Â